Oral health and erectile dysfunction - Vijendra P Singh; Sunil K Nettemu; Sowmya Nettem; Rajesh Hosadurga; Sangeeta U Nayak (Wolters Kluwer Medknow Publications, 2017)
Ample evidence strongly supports the fact that periodontal disease is a major risk factor for various systemic diseases namely cardio-vascular disease, diabetes mellitus, etc. Recently, investigators focussed on exploring the link between chronic periodontitis (CP) and erectile dysfunction (ED) by contributing to the endothelial dysfunction. Both the diseases share common risk factors. Various studies conducted in different parts of the world in recent years reported the evidence linking this relationship as well as improvement in ED with periodontal treatment. Systemic exposure to the periodontal pathogen and periodontal infection-induced systemic inflammation was thought to associate with these conditions. The objective of this review was to highlight the evidence of the link between CP and ED and the importance of oral health in preventing the systemic conditions.